Bacteriology and Antibiotic Susceptibility Patterns among Neonates Diagnosed of Omphalitis at a Tertiary Special Care Baby Unit in Western Uganda - Munanura Turyasiima; Martin Nduwimana; Gloria Kiconco; Walufu Ivan Egesa; Silva Andres Manuel; Peter Kalubi; Yamile Enedina Arias Ortiz (Hindawi Limited, 2020)
Background. Newborn infections remain a major cause of morbidity and mortality among neonates in low-income countries. Clinical diagnosis for omphalitis in such settings is possible but this does not depict the microbiological characteristics of the involved organisms, and clinicians have often prescribed empirical antibiotics in neonates with omphalitis, despite an increasing burden of antibiotic resistance. Methods. A hospital-based cross-sectional study was conducted to evaluate the bacteriology and antibiotic susceptibility patterns among neonates diagnosed with omphalitis at the special care baby unit (SCBU) of Kampala International University-Teaching Hospital (KIU-TH), western Uganda from March to June 2019. Sixty-five (65) neonates with a clinical diagnosis of omphalitis were consecutively recruited in the study. Cord swabs were taken under sterile (aseptic) precautions from all neonates, and antibiotic susceptibility tests performed using the Kirby Bauer disk diffusion technique with commercially available antibiotics disks of ampicillin, cloxacillin, gentamicin, amikacin, cefotaxime, ceftriaxone, vancomycin, and imipenem on Mueller Hinton agar plates. The data was analyzed using STATA version 13.0, frequencies and proportions used to describe the variables. Results. Fifty-five, 55 (84.6%), neonates with suspected omphalitis had positive cord swab culture. Staphylococcal aureus (58.2%) was the commonest cause of omphalitis followed by Neisseria spp (16.4%), E. coli 6 (10.9%), Proteus spp (5.5%), Klebsiella spp (3.6%), Citrobacter spp (3.6%), and Haemophilus spp (1.8%) in decreasing frequency. Isolates were resistant to ampicillin (87.7%), gentamicin (54.4%), and cloxacillin (34.4%), the drugs recommended for use in neonates with suspected omphalitis. Conclusions. Staphylococcal aureus is still the predominant cause of omphalitis among neonates. There was high resistance to the commonly used antibiotics in the treatment of omphalitis among newborns. This study reemphasizes that clinicians should do cord swabbing for both culture and susceptibility tests among newborns with suspected omphalitis before initiation of antibiotics.